Lactato sangüineo em provas combinadas e isoladas do triatlon: Possiveis implicavcoes para o desempenho - Costa, J. M. P.; Kokubun, E. (Revista Paulista Educação Física, 1995)
In an attempt to understand the blood lactate response to the triathlon, and its effects upon the performance, eight male triathletes were submitted to three test sessions. In the former, the subjects did a complete race session, which consisted of: 750 m swimming, 20 km cycling and 5 km running. In the later two sessions (isolated) they did the cycling or the running after, at least, 24 hours rest. During the transitions in the first session and after the completion of all sessions, blood was taken for lactate analysis. The cycling and running speeds were greater in the isolated than the complete session (respectively, 4.1% and 8.0%). The mean blood lactate ranged from 6.68 to 9.11 mM but no significant difference was detected between the sessions. However, the time and lactate differences in the isolated and complete race were inversely correlated (r = -0.53). These findings suggest that the decreased performance in the complete race is due to the elevated acidosis resulting from any of the triathon events.